2009
DOI: 10.1105/tpc.109.069997
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisWUSCHEL Is a Bifunctional Transcription Factor That Acts as a Repressor in Stem Cell Regulation and as an Activator in Floral Patterning

Abstract: Most transcription factors act either as activators or repressors, and no such factors with dual function have been unequivocally identified and characterized in plants. We demonstrate here that the Arabidopsis thaliana protein WUSCHEL (WUS), which regulates the maintenance of stem cell populations in shoot meristems, is a bifunctional transcription factor that acts mainly as a repressor but becomes an activator when involved in the regulation of the AGAMOUS (AG) gene. We show that the WUS box, which is conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
254
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(271 citation statements)
references
References 35 publications
15
254
1
1
Order By: Relevance
“…2C). Mutation of two amino acids (leucine-to-alanine exchange) in the WUS-box of STF (STFm1), similar to that reported by Ikeda et al (19), partially relieved this repression ( Fig. 2 A-C), suggesting that STF is a transcriptional repressor and that its WUS-box is at least partially responsible for mediating the repressive activity.…”
Section: Stf Acts As a Transcriptional Repressor In Regulating Leaf Bsupporting
confidence: 61%
“…2C). Mutation of two amino acids (leucine-to-alanine exchange) in the WUS-box of STF (STFm1), similar to that reported by Ikeda et al (19), partially relieved this repression ( Fig. 2 A-C), suggesting that STF is a transcriptional repressor and that its WUS-box is at least partially responsible for mediating the repressive activity.…”
Section: Stf Acts As a Transcriptional Repressor In Regulating Leaf Bsupporting
confidence: 61%
“…Previous work showed that RA1's two EAR motifs interact with a protein encoded by ramosa enhancer locus2, an ortholog of the corepressor TOPLESS (Gallavotti et al 2010). While EAR motifs may confer repressive activity to TFs (Kagale and Rozwadowski 2011), there are examples where transcriptional repressors, such as the stem cell regulator WUSCHEL, activate gene expression in specific developmental contexts (Ikeda et al 2009). Activated and repressed targets of RA1 were partitioned both developmentally and temporally, suggesting the mechanism of RA1 action depends on spatiotemporal context.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that ARR1, ARR10, and ARR12 exhibit dual functions in transcription regulation and activate the transcription of WUS and repress that of YUCs within the same cell niche. WUS has previously been shown to have a similar dual function (Ikeda et al, 2009). It is possible that different partner proteins interacting with ARRs confer their functions as either transcriptional activators or repressors.…”
Section: Arr1 Arr10 and Arr12 Are Bifunctional Transcription Factormentioning
confidence: 99%